Factors that affecting mental health among 3rd year fhpk students at universiti malaysia kelantan, city campus - Nurul Aisyah Ibrahim; Nurul Syaadah Chik; Sharifah Nurul Hayati Syed Anuar; Siti Zulaikha Zolkurnain (2022)
Mental health is important for every stage of life including childhood, teenagers, adults, and others. There are many effects that can lead to mental health issues among university students. Mental health among students is increasingly concerned and very important for students because it’s related to emotional, psychological also social well-being. The study is focusing on the factors that cause mental health among 3rd year FHPK student at University Malaysia Kelantan, City Campus which is to identify the effect of time management on mental health among 3rd year students at University Malaysia Kelantan, City Campus, to determine the effect of environment on mental health among 3rd year students at University Malaysia Kelantan, City Campus and to examine the effect of lifestyle factor on mental health among 3rd year students at University Malaysia Kelantan, City Campus. The study was conducted using a quantitative research approach which is through online questionnaire to collect the data. There were 250 respondents participated in the study which had been conducted through social media such as WhatsApp group and it focused on the third years FHPK students in Universiti Malaysia Kelantan, City Campus. Keywords: Mental Health, Time Management, Lifestyle, Environment